“Sermo eorum sicut cancer serpit”. Chromatius of Aquileia against heresies - Sajovic, Miran (Vox Patrum, 2018)
Bishop Chromatius (in office from 388 to 407), whose episcopal see was a cosmopolitan trade-center at the north end of the Adriatic Sea with the name of Aquileia, was one of the most prominent bishops in the period. He is acquainted with notable figures such as Ambrosius, Hieronymus, Rufinus, and Ioannes Chrysostomus and forth. Before being created a bishop, he was the secretary of bishop Valerianus and in the occasion of Council of Aquileia in 381, he had spoken against Arians. This Council was presided by Ambrosius and with its scale it could almost be considered as an ecumenical one. As shown in some of the Chromatius’ sermons, which are unearthed in the 20th century, he opposed not only to the ideas of Arians but also to the teaching of Fotinus, bishop of Sirmium. Chromatius was a very zealous fighter and he practically succeeded to uproot all heretical ideas in his diocese. The academia usually sees him as an anti-Arian theologian. After the Council of Constantinople (381), the Arian heresy seemed to be abated, but Chromatius said in one of his Tractatus, “Cuius (sc. Arii) discipuli hodieque oues Dei fallere ac decipere conantur per aliquantas ecclesias, sed iamdudum, magistro perfidiae prodito, discipuli latere non possunt”; it is evident that, the followers of Arius could still be found (with the mentioning of “hodie”, i.e. today) in the area of Aquileia, meanwhile one must not neglect the presence of the followers of Fotinus of Sirmium. The first part of my conference paper would be a general presentation of the religious situation in Aquileia at the time where Chromatius served as the local bishop; thus I will proceed with an in-depth reading on several passages of the Aquilerian bishop’s sermons (Sermones and Tractatus), in order to show the impact of the those heresies on his works and to identity his theological arguments against them. Among those teachings, there is the “unconquerable faith (invicta fide)”, which led to the surmounting (suppression) of heresies.